Chosen aspects of information management in IT outsourcing - Sobińska, Małgorzata (Wybrane aspekty zarządzania informacją w outsourcingu IT, 2011)
Outsourcing, including the IT outsourcing, is one of the most frequently chosen business tools in the contemporary management practice. The aim of this article is discussing chosen aspects of information management in outsourcing projects, which, according to the author, has a huge impact on the shape and course of cooperation with the external IT services provider. Special attention will be paid to analysing information needs, managing documentation and the rules of communication in outsourcing projects. The choice of the topic is relatedto the author’s conviction that the discussed management aspects are often neglected by organizations choosing to cooperate with the external IT services providers
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics, 2011, Nr 205, s. 240-247
Keywords: IT outsourcing; information management; information needs; SLA agreements; communication